Bridging Digital and Traditional Classrooms: Students’ Views on Online and Offline Teaching in Punjab - Khosla, Manisha; Batra, Gurdeep Singh; Dwivedi, Sulakshna (Journal of Advanced Research in Humanities and Social Sciences; Vol 12 No 1 (2025): Journal of Advanced Research in Humanities and Social Sciences, 2025)
This study investigates students’ perceptions of online and offline teaching modes in state universities in Punjab, focusing on students from five departments: Management, Computer Science, Engineering, Pharmacy, and Hotel Management. A sample of 720 students from five major state universities was surveyed to examine their perception regarding online and offline teaching modes. The study reveals that students generally prefer offline learning, citing higher satisfaction with course outcomes, personal engagement, and instructor feedback. However, a significant number of students (45.7%) favoured blended learning, a combination of online and offline methods, indicating a desire for a flexible, interactive learning environment. Online learning, despite its flexibility and cost-effectiveness, was associated with challenges such as lower engagement, isolation, and difficulties in obtaining timely feedback. The study also highlights the importance of fair assessments, the use of social media platforms for collaborative learning, and usability features in learning management systems (LMS) to enhance the online learning experience. Additionally, students indicated the need for improved technological support, personalised feedback, and instructor training to enhance online learning. Based on these findings, the study suggests that educational institutions should focus on integrating blended learning models, enhancing online engagement, and addressing technological barriers. The findings underscore the importance of adapting teaching strategies to create a more engaging and effective learning environment.